Serum‐free bioprocessing of adult human and rodent skin‐derived Schwann cells: implications for cell therapy in nervous system injury. (8th February 2017) - Mirfeizi, Leila; Stratton, Jo Anne; Kumar, Ranjan; Shah, Prajay; Agabalyan, Natacha; Stykel, Morgan G.; Midha, Rajiv; Biernaskie, Jeff; Kallos, Michael S.
Abstract: Peripheral nerve injury affects 2.8% of trauma patients with severe cases often resulting in long‐lived permanent disability, despite nerve repair surgery. Autologous Schwann cell (SC) therapy currently provides an exciting avenue for improved outcomes for these patients, particularly with the possibility to derive SCs from easily‐accessible adult skin. However, due to current challenges regarding the efficient expansion of these cells, further optimization is required before they can be seriously considered for clinical application. Here, a microcarrier‐based bioreactor system is proposed as a means to scale‐up large numbers of adult skin‐derived SCs for transplantation into the injured nerve. Bioprocessing parameters that allow for the expansion of adult rodent SCs have been identified, whilst maintaining similar rates of proliferation (as compared to static‐grown SCs), expression of SC markers, and, importantly, their capacity to myelinate axons following transplant into the injured sciatic nerve. The same bioprocessing parameters can be applied to SCs derived from adult human skin, and like rodent cells, they sustain their proliferative potential and expression of SC markers. Taken together, this dataset demonstrates the basis for a scalable bioprocess for the production of SCs, an important step towards clinical use of these cells as an adjunct therapy for nerve repair. Copyright © 2017 John Wiley & Sons, Ltd.